2013
DOI: 10.1016/j.jams.2013.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Amygdaloid Corticotropin-releasing Factor is Involved in the Anxiolytic Effect of Acupuncture during Ethanol Withdrawal in Rats

Abstract: In a previous study, acupuncture at acupoint HT7 attenuated ethanol withdrawal-induced anxiety-like behavior in rats by normalizing amygdaloid catecholamines. In the present study, the involvement of amygdaloid corticotropin-releasing factor (CRF) in the anxiolytic effect of acupuncture was investigated during ethanol withdrawal. Rats were intraperitoneally treated with 3 g /kg/day of ethanol for 28 days, and the CRF mRNA levels in the central nucleus of the amygdala (CEA) were measured by using a RT-PCR analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
2
11
0
Order By: Relevance
“…that the selective NEergic alpha1 receptor antagonist prazosin concurrently blocks the anxiety and the increase in ethanol intake induced by EW, reflecting the positive correlation between the NEergic system and the HPA in the regulation of ethanol consumption. The simultaneous hyperactivation of NE and CRF in the central nervous system during EW has also been demonstrated in our previous studies showing elevated activation in both amygdaloid NE and CRF during EW [8,9]. Additionally, in a recently published study, we also reported increased CRF protein expression in the rat PVN 24 hours after cessation of ethanol administration [12].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…that the selective NEergic alpha1 receptor antagonist prazosin concurrently blocks the anxiety and the increase in ethanol intake induced by EW, reflecting the positive correlation between the NEergic system and the HPA in the regulation of ethanol consumption. The simultaneous hyperactivation of NE and CRF in the central nervous system during EW has also been demonstrated in our previous studies showing elevated activation in both amygdaloid NE and CRF during EW [8,9]. Additionally, in a recently published study, we also reported increased CRF protein expression in the rat PVN 24 hours after cessation of ethanol administration [12].…”
Section: Discussionsupporting
confidence: 85%
“…Acute ethanol increases hypothalamic NE neosynthesis [4] and plasma corticosterone (CORT) secretion [5], and chronic ethanol can produce elevated blood glucocorticoid levels as well as increased activity in the sympathetic nervous system [6]. Dar and Wooles [7] have reported increased hypothalamic NE concentrations in EW mice, and we have also demonstrated that EW raises amygdaloid NE and CRF mRNA levels in rats [8,9].…”
Section: Introductionmentioning
confidence: 69%
“…Amygdaloid CRF1R, but not CRF2R, mediates anxiety-like behavior in mouse EPM tests [ 36 , 37 ] and activation of CRF1R, but not CRF2R, in the CeA affects ethanol withdrawal-induced anxiety in rats [ 38 ]. A previous study by our research group revealed that ethanol withdrawal increases CRF mRNA expressions in the rat CeA [ 39 ]. In the present study, real-time PCR and Western blot analyses displayed increased protein and mRNA expressions for both CRF and CRF1R in the CeA of rats undergoing NicW, which are consistent with the studies done by others showing that NicW robustly increases the mRNA levels of CRF and CRF1R in the CeA [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructural and pharmacological analyses have revealed that CRF neurons in the CeA are targeted by noradrenergic afferents [ 41 ], that NE is a secretagogue of CRF, and that the activation of β -adrenergic receptors appears to stimulate CRF gene expression in the extended amygdala [ 15 , 42 ]. Our previous studies have shown ethanol withdrawal simultaneously elevates noradrenergic transmission and CRF mRNA expression in the CeA [ 17 , 39 ]; in addition, the studies done by others have also identified the parallel functional promotion of the noradrenergic and CRFergic systems in the CeA following the cessation of the chronic abuse of drugs [ 43 , 44 ]. Accordingly, in the present study, NicW significantly increased both NE and MHPG levels in the CeA, whereas the administration of 180 mg/kg/d AESZS prevented these increases.…”
Section: Discussionmentioning
confidence: 99%
“…and stainless steel guide cannulae (15 mm; 23 gauge) were bilaterally implanted into the amygdala using a stereotaxic instrument with the cannula tips 2 mm above the CeA using the same coordinates described above [15] . The guide cannulae were secured in place using two small stainless steel screws anchored to the skull with dental acrylic cement [16] . Animals were allowed 7 d of recovery following the surgery.…”
Section: Methodsmentioning
confidence: 99%